STRIDER NZAus: a multicentre randomised controlled trial of sildenafil therapy in early‐onset fetal growth restriction. (14th March 2019) - Groom, KM; McCowan, LM; Mackay, LK; Lee, AC; Gardener, G; Unterscheider, J; Sekar, R; Dickinson, JE; Muller, P; Reid, RA; Watson, D; Welsh, A; et al.
Abstract : Objective: To assess the effect of maternal sildenafil therapy on fetal growth in pregnancies with early‐onset fetal growth restriction. Design: A randomised placebo‐controlled trial. Setting: Thirteen maternal–fetal medicine units across New Zealand and Australia. Population: Women with singleton pregnancies affected by fetal growth restriction at 22 +0 to 29 +6 weeks. Methods: Women were randomised to oral administration of 25 mg sildenafil citrate or visually matching placebo three times daily until 32 +0 weeks, birth or fetal death (whichever occurred first). Main Outcome Measures: The primary outcome was the proportion of pregnancies with an increase in fetal growth velocity. Secondary outcomes included live birth, survival to hospital discharge free of major neonatal morbidity and pre‐eclampsia. Results: Sildenafil did not affect the proportion of pregnancies with an increase in fetal growth velocity; 32/61 (52.5%) sildenafil‐treated, 39/57 (68.4%) placebo‐treated [adjusted odds ratio (OR) 0.49, 95% CI 0.23–1.05] and had no effect on abdominal circumference Z ‐scores ( P = 0.61). Sildenafil use was associated with a lower mean uterine artery pulsatility index after 48 hours of treatment (1.56 versus 1.81; P = 0.02). The live birth rate was 56/63 (88.9%) for sildenafil‐treated and 47/59 (79.7%) for placebo‐treated (adjusted OR 2.50, 95% CI 0.80–7.79); survival to hospital discharge free of major neonatal morbidity was 42/63 (66.7%) for sildenafil‐treated and 33/59 (55.9%) for placebo‐treated (adjusted OR 1.93, 95% CI 0.84–4.45); and new‐onset pre‐eclampsia was 9/51 (17.7%) for sildenafil‐treated and 14/55 (25.5%) for placebo‐treated (OR 0.67, 95% CI 0.26–1.75). Conclusions: Maternal sildenafil use had no effect on fetal growth velocity. Prospectively planned meta‐analyses will determine whether sildenafil exerts other effects on maternal and fetal/neonatal wellbeing. Tweetable abstract: Maternal sildenafil use has no beneficial effect on growth in early‐onset FGR, but also no evidence of harm. Tweetable abstract: Maternal sildenafil use has no beneficial effect on growth in early‐onset FGR, but also no evidence of harm.